Calculation of pipe bend and tension in case of fluid velocity pulsation - Didžgalvis, Rimantas; Sudintas, Antanas; Tiknevičienė, Irena (Lietuvos matematikos rinkinys, 2000)
The mathematical model of a bend pipe with a flowing fluid at a fluid pulsation was created. By solving differential equations, an analytical expression of solution is received, which may be well used for calculation of normal tension of the pipe at different ground load quantities and flow velocity pulsation. The received results allow a more precise evaluations of mechanical resource of the pipe at the complicated loads.